Specificity in the relationship between training and performance in triathlons - Hendy, H. M.; Boyer, B. J. (Perceptual and Motor Skills, 1995)
The present study examines whether swim, cycle, and run performance during a triathlon are predicted best by training in the same sport, as suggested by the theory of specificity for the relationship between sport training and performance. Using behavioral measures of training (pace, mileage, workouts), multiple regression analyses of questionnaire responses from 624 triathletes (443 men, 181 women) showed pace of training in the same sport to be the best predictor of swim and run performance for both sprint and endurance triathlons. No clear patterns were seen for cycle performance. Thus, specificity in the relationship between training and performance appears supported, especially for sports that rely more on the body (swim, run) and less on equipment (cycle).